2018
DOI: 10.5505/ejm.2018.32932
|View full text |Cite
|
Sign up to set email alerts
|

Problems encountered in screening study with ultrasound for early diagnosis of developmental dysplasia of hip in eastern region of Turkey

Abstract: The aim of this study is to evaluate results of the screening program of the development al dysplasia of the hip (DDH) examined in newborn period. The problems encountered in the applicability of the early screening program were e valuated. By interviewing with the family of 1680 newborns born in our institution or referred, the information was given about the DDH and its risk factors, obtained results were recorded. The families were told to bring their babies for examination and hip ultrasound at the 3 rd or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…36 Despite efforts in Turkey to educate parents about the risks of tight swaddling of lower extremities, one institution reported that approximately 75% continued to swaddle their babies with legs extended. 37 In Qatar, the implementation of a community awareness program demonstrating the harmful effects of swaddling reduced the incidence of ultrasonographic dysplasia in children at high risk for DDH from 20% to 6%. 38 Ultrasound has also been used to evaluate hip joint stability in infants who were swaddled by the traditional tight method, safe blanket techniques, and commercial devices.…”
Section: Other Post-natal Positioning and Effects On Hip Developmentmentioning
confidence: 99%
“…36 Despite efforts in Turkey to educate parents about the risks of tight swaddling of lower extremities, one institution reported that approximately 75% continued to swaddle their babies with legs extended. 37 In Qatar, the implementation of a community awareness program demonstrating the harmful effects of swaddling reduced the incidence of ultrasonographic dysplasia in children at high risk for DDH from 20% to 6%. 38 Ultrasound has also been used to evaluate hip joint stability in infants who were swaddled by the traditional tight method, safe blanket techniques, and commercial devices.…”
Section: Other Post-natal Positioning and Effects On Hip Developmentmentioning
confidence: 99%